A influência do consumo no design brasileiro do século 19: uma revisão teórica - Toledo, Emmanuel Guedes de [UNESP] (2014)
This study consists in a literature review on the history of design and focuses on understanding the connections between consumption and practice of design in Brazil in the 19th century. From the textual, thematic and interpretative analysis of a chosen material through a literature review and technical reading, some aspects of consumption and design are identified in Brazil during such period, to then discuss the relevance of consumption for understanding manifestations of design activity in Brazil. The analyzes are based on a literature review that approaches aspects of the articulation between design and consumption as commmodity fetishism, the dynamics of the print market in the industrial era, the establishment of department stores in European urban centers and the manufacturing of articles of luxury in the 18th century. It is observed that some of the main directions of design in its history in the modern world and in Brazil in the nineteenth-century, can be understood through social and cultural aspects revealed from the consumption of industrialized artifacts